MODEL SISTEM DINAMIK KETERSEDIAAN MINYAK GORENG BERBASIS CPO UNTUK MENDUKUNG KETAHANAN PANGAN - Faradiba Aurel Yasmin; Mifa Amira Dewi; Keysha Naila Chadijah; Mafda Khoirotul Fathah (CV. Adiba Aisha Amira, 2026)
Cooking oil is a basic necessity that plays an important role in supporting food security in Indonesia. Although Indonesia is one of the largest producers of crude palm oil (CPO) in the world, the availability of cooking oil in the domestic market still faces various problems, such as price fluctuations and supply imbalances. These problems are influenced by various interrelated factors, including production, exports, consumption, distribution, and government policies. This study aims to analyze the availability of CPO-based cooking oil using a system dynamics approach, the method used is a causal loop diagram (CLD) to systematically map the cause-and-effect relationship among variables in the system. The results of the analysis indicate that the cooking oil availability system is complex and dynamic, with the presence of a feedback relationship in the form of reinforcing and balancing loops. Variables such as CPO production, exports, consumption, and prices play an important role in influencing cooking oil availability. The resulting model can be used as a tool to comprehensively understand system behavior, as well as a basis for policy formulation to maintain supply stability and support national food security.